Association of duration of treatment on post-discharge mortality in forensic psychiatric patients in Finland - Ojansuu, Ilkka; Forsman, Jonas; Kautiainen, Hannu; Seppänen, Allan; Tiihonen, Jari; Lähteenvuo, Markku (Frontiers in Psychiatry, 2024)
Background Longer treatment time has been shown to be associated with lower crime recidivism among forensic psychiatric patients, but it is not known if this applies also to mortality. In this study, we aim to research whether treatment time is associated with risk of post-discharge mortality in Finnish forensic psychiatric patients. Materials and methods The study population consisted of 989 patients committed to compulsory forensic psychiatric hospital treatment in Finland from 1980 to 2009 who were released from care by the end of 2018. Each patient included in the cohort was linked with the Statistics Finland register, which includes all data on dates and causes of deaths in Finland. Crude cumulative rate of mortality were estimated using Kaplan–Meier method and compared using logrank-test. Adjusted cumulative rate analyzed using Cox regression model. A possible nonlinear relationship between the treatment time and the hazard of death was assessed by using 3-knot-restricted cubic spline regression. Adjusted models included age, sex, and SUD (substance use disorder) as covariates. Results The mean duration of care was 7.1 (SD 6) years. The duration of treatment variable was divided into tertiles of treatment duration less than 3.5 years, 3.5–7.9 years and equal or more than 8 years. The risk of mortality was highest in the first tertile, and lowest in the last tertile. The risk of mortality was higher for patients suffering from SUD, for patients of male sex and for those released at younger age. Conclusions Longer treatment time is associated with reduced post-discharge mortality in forensic psychiatric patients in Finland. Especially males and individuals with SUD are at higher mortality risk after release, but longer treatment duration may mitigate these risks. Longer periods of hospitalization have to be, however, viewed against the backdrop of institutionalization and loss of self-determination.